Application of Problem Based Learning Model to Increase Activeness and Learning Outcomes in Junior High School Statistics Learning - Wahid Wahyudhi; Sugiarto Pudjohartono; Agus Margono; Laila Fitriana (Universitas Sebelas Maret, 2023)
Learning in class VIII students often have difficulty identifying solutions to real problems related to statistics such as mean, median, and mode. In addition, students also often experience inaccuracies in doing calculations. Therefore, classroom action research is carried out with the aim of increasing activeness and learning outcomes through the use of problem based learning learning models. The subjects of this study were students of class VIII A of SMP Negeri 1 Adimulyo, totaling 32 students. The activity data was collected by the observation method, and the learning outcome data was collected by the test method. The test data were analyzed based on the answer key and the predetermined scoring rubric. The activity data was analyzed based on the percentage of students who showed active responses such as: in asking the teacher's questions, doing practice questions, and answering questions. Indicators of the success of learning outcomes are determined by 70% of students achieving the minimum completeness criteria (KKM), and 50% of student activeness. During these two research cycles, learning outcomes increased from 21.87% to 45.16% (in the first cycle) and 74.19% at the end of the second cycle. Meanwhile, student activity increased from 18.75% in cycle 1 to 40.85% at the end of cycle 2. Although activity was not as expected, the increase in student activity obtained gave new hope for improving the quality of teaching and learning in schools.